Efficient synthesis of azetidine-2,3-diones from L-(+)-diethyl tartrate - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synlett, 2007)
A convenient route to enantiopure azetidine-2,3-diones is described. The chiral ketene generated from commercially available L-(+)-diethyl tartrate on Staudinger cycloaddition with different imines gave spiro-beta-lactams in good yields. These spiro-beta-lactams were transformed into azetidine-2,3-diones in excellent yields in a two-step process.
Keywords: Cycloaddition; imines; lactams; spiro compounds; stereoselective synthesis

Simple synthesis of the novel antihistaminic drug olopatadine hydrochloride - Chavan, Subhash P.; Lasonkar, Pradeep B. (Synthesis-Stuttgart, 2013)
A new alternative route for the synthesis of olopatadine is described. The present strategy involves a Lewis acid mediated ring opening of a cyclic ether to introduce 3-(dimethylamino)propylidene group as the side chain.
Keywords: antihistaminic drugs; chelates; Lewis acids; spiro compounds; zinc

Enantioselective synthesis of spirocyclohexadienones by NHC-catalyzed formal [3+3] annulation reaction of enals - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
The enantioselective synthesis of pyrazolone-fused spirocyclohexadienones was demonstrated by the reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones under oxidative N-heterocyclic carbene (NHC) catalysis. This atom-economic and formal [3+3] annulation reaction proceeds through a vinylogous Michael addition/spiroannulation/dehydrogenation cascade to afford spirocyclic compounds with an all-carbon quaternary stereocenter in moderate to good yields and excellent ee values. Key to the success of the reaction is the cooperative NHC-catalyzed generation of chiral alpha,beta-unsaturated acyl azoliums from enals, and base-mediated tandem generation of dienolate/enolate intermediates from pyrazolinones.
Keywords: annulation reactions; asymmetric catalysis; N-heterocyclic carbenes; organocatalysis; spiro compounds

Unified approach to fused and spirocyclic oxindoles through lewis-acid-promoted opening of spiroepoxyoxindoles with allylsilanes: application to the formal synthesis of (+/-)-physovenine - Sharma, Brijesh M.; Yadav, Mahesh; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2017)
A protocol for the construction of oxindoles containing all-carbon quaternary centres in a highly regioselective manner has been developed. The reaction involves opening of spiroepoxyoxindoles with allylsilanes to give Hosomi-Sakurai-type products as well as new silicon-containing spirocyclic oxindoles. A formal synthesis of (+/-)-physovenine was accomplished in five steps using this protocol.
Keywords: alkaloids; Allylation; annulation; Lewis acids; spiro compounds

Unlocking thermodynamic enolate for kinetically controlled desymmetrizing vinylogous (4+1) carbospiroannulation - Singh, Sanjay; Singh, Abhijeet; Pandya, Rinu; Vanka, Kumar; Singh, Ravi P. (Chemistry-A European Journal, 2025)
An unprecedented thermodynamically unfavorable (4+1) deysmmetrizing spiroannulation through a thermodynamic enolate intermediate, enabling a single-step synthesis of ubiquitous scaffolds such as all-carbon chiral spirocycles, is disclosed. In this spiroannulation, we present a vinylogous organocatalytic enantioselective desymmetrizing (4+1) cycloaddition approach involving alkylidene malononitrile and cyclopent-1,3-dienone. This carbospiroannulation method produces functionally enriched spiro[4,4]nonane structures with three stereocenters, has presented good-to-high yields and enantiomeric ratios. Detailed DFT calculations reveal an intriguing reaction mechanism, which validates our observations.
Keywords: 3-diones; alkylidene malononitrile; cyclopent-1; quaternary stereocenters; spiro compounds; thermodynamic enolate